Basic evaluation of Pentra MS CRP, a new automated hematology analyzer for rapid 5‐part WBC differential and CRP using a small volume of whole blood. (11th June 2014) - Inaba, T.; Nomura, N.; Ishizuka, K.; Yoshioka, K.; Takahashi, M.; Yuasa, S.; Saito, K.; Fujitomo, Y.; Nakanishi, M.; Fujita, N.
Summary Introduction Pentra MS CRP is a new automated hematology analyzer that can rapidly and reliably provide 5‐part differential of leukocytes (5‐Diff) and C‐reactive protein (CRP) within approximately 3.5 min using a small volume of whole blood (35 μL). Methods We evaluated the basic performance of Pentra MS CRP and correlations with Sysmex XN‐3000, manual microscopic count, and Hitachi LABOSPECT. Results Pentra MS CRP demonstrated good repeatability and linearity without any significant carryover for all parameters examined (WBC, RBC, HGB, Hct, PLT, 5‐Diff, and CRP). Complete blood cell count (CBC) data examined by Pentra MS CRP correlated well with those evaluated by Sysmex XN‐3000 (R ≥ 0.9880). Absolute number of NEU, LYM, and EOS also showed the good correlation (R ≥ 0.9866) between the two analyzers. The correlation with the manual microscopic count was within acceptable criteria. Furthermore, when CRP was examined in hemolyzed whole blood by Pentra MS CRP and converted to plasma concentrations according to Hct, it correlated well (R = 0.9964) with serum CRP examined by Hitachi LABOSPECT. Conclusion Pentra MS CRP is a convenient and reliable analyzer especially in the emergency unit of hospitals in which the prompt and simultaneous measurement of CBC including 5‐Diff and CRP is often necessary.